Effects of dietary protein supplementation and infection with gastrointestinal nematode parasites on some nutritional and metabolic parameters in Ethiopian Menz and Horro sheep - Haile, Aynalem; Anindo, D.O.; Tembely, S.; Mukasa-Mugerwa, E.; Tibbo, Markos; Yami, A.; Baker, R.L.; Rege, J.E.O. (Elsevier, 2004)
The effect of subclinical artificial nematode parasite infection on dry matter intake (DMI), apparent digestibility (AD), efficiency of feed utilisation (EFU), plasma protein (PPC) and albumin concentrations (AC) was examined in lambs of the Horro and Menz breeds. The factorial experimental design involved two breeds, two infection treatments (infected vs. noninfected) and three nutrition treatments [hay plus wheat bran (basal diet), hay plus molasses urea block (MUB), hay plus cotton seed cake (CSC)]. Diets were formulated to be isocaloric but with varying protein and/or nitrogen sources. At the start of the study, 152 lambs (103 Menz and 49 Horro) were assigned to the 12 treatment combinations each in a separate pen, with an average of about 13 animals per pen. Challenge with endoparasites involved three infection periods each separated by an anthelmintic treatment. The first two infections were with Haemonchus contortus while the third infection was with a mixed infection of H. contortus, Longistrongylus elongata and Trichostrongylus colubriformis. Infected lambs had lower total DMI, EFU (not significant in third infection), AD (significant only in third infection) and total PPC and AC than noninfected lambs. Horro lambs had higher DMI and EFU but lower AD than Menz lambs. PPC was significantly higher in lambs supplemented with CSC compared to those on the basal diet or supplemented with MUB in the primary and secondary infections; but during the tertiary infection, no significant differences were found. AC was significantly greater in CSC-supplemented lambs than those on the basal diet or supplemented with MUB. It was concluded that subclinical nematode infection had an adverse effect on feed intake, efficiency of feed utilisation and apparent digestibility. Infection was also found to cause hypoproteinaemia and hypoalbuminaemia. Protein supplementation would help mitigate the effects of infection on total plasma protein and albumin concentrations, especially in the low-input systems typified by the Ethiopian highlands.